2021
DOI: 10.2337/figshare.13516922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exocrine Pancreatic Enzymes Are a Serological Biomarker for Type 1 Diabetes Staging and Pancreas Size

Abstract: Exocrine pancreas abnormalities are increasingly recognized as features of type 1 diabetes. We previously reported reduced serum trypsinogen levels and in a separate study, smaller pancreata at and prior to disease onset. We hypothesized that three pancreas enzymes (amylase, lipase and trypsinogen) might serve as serological biomarkers of pancreas volume and risk for type 1 diabetes. Amylase, lipase, and trypsinogen were measured from two independent cohorts, together comprising 800 serum samples from single-a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2021, the same team of investigators expanded their studies to trypsinogen, lipase, and amylase in a larger cohort. They showed that trypsinogen and lipase are significantly reduced in subjects with established and recent-onset diabetes, and in individuals with multiple islet autoantibodies compared with single islet autoantibody positive and control subjects (70). In contrast, amylase levels were reduced only in patients with established T1D.…”
Section: Enzymes Of the Exocrine Pancreas As Biomarkers In T1dmentioning
confidence: 99%
“…In 2021, the same team of investigators expanded their studies to trypsinogen, lipase, and amylase in a larger cohort. They showed that trypsinogen and lipase are significantly reduced in subjects with established and recent-onset diabetes, and in individuals with multiple islet autoantibodies compared with single islet autoantibody positive and control subjects (70). In contrast, amylase levels were reduced only in patients with established T1D.…”
Section: Enzymes Of the Exocrine Pancreas As Biomarkers In T1dmentioning
confidence: 99%
“…Serum trypsinogen and lipase levels can successfully categorize individuals as having ≥ 2 islet autoantibodies versus 1 and are an effective indicator of BMI-normalized relative pancreas volume by magnetic resonance imaging (MRI) [17]. Additionally, pancreas volume by MRI is smaller in T1D first degree relatives, islet autoantibody positive, and recent-onset T1D individuals versus controls respectively [5].…”
Section: Using Exocrine Biomarkers In Disease Prediction and Monitoringmentioning
confidence: 99%